Application of genetic algorithms to construction scheduling with or without resource constraints - Toklu, YC (Natl Research Council Canada, 2002)
The difficulties encountered in scheduling construction projects with resource constraints are highlighted by means of a simplified bridge construction problem. A genetic algorithm applicable to projects with or without resource constraints is described. In this application, chromosomes are formed by genes consisting of the start days of the activities. This choice necessitated introducing two mathematical operators (datum operator and left compression operator) and emphasizing one genetic operator (fine mutation operator). A generalized evaluation of the fitness function is conducted. The algorithm is applied to the example problem. The results and the effects of some of the parameters are discussed.
Keywords: scheduling; genetic algorithms; construction management; computer application